SURVEY OF THE TECHNIQUES OF RAPID SEQUENCE INTUBATION BY PRACTICING ANESTHESIOLOGISTS IN TERTIARY CARE HOSPITALS OF KARACHI - A CROSS-SECTIONAL SURVEY - Dr. Muhammad Waqas Khan,; Dr.Syed Hassan Adil Rizvi,; Dr. Komal Zafar,; Dr. Atif Parvez,; Dr. Asir Nasiruddin,; Sajid Atif Aleem, (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Rapid Sequence Induction (RSI) is a key technique to reduce aspiration risk during emergency surgeries, involving preoxygenation, intravenous anesthesia, cricoid pressure, and rapid intubation without mask ventilation. Debate persists over optimal positioning and cricoid pressure application, with variations in practice. While some believe preoxygenation suffices for low-risk patients, others stress strict protocols for safety. Further research on these discrepancies could help standardize techniques and reduce this preventable complication.Objective To evaluate the techniques of Rapid Sequence Intubation (RSI) among anesthesiologists in tertiary care hospitals of Karachi and identify variations in practice.Materials and Method: This cross-sectional investigation, performed from November 2021 until May 2022 across nine tertiary medical centers in Karachi, aimed to assess anesthesia practices among 87 anesthesiologists. Employing a non-random, successive sampling method, the research targeted consultants, specialists, and final-year FCPS residents. Information was collected through self-administered questionnaires regarding demographics and anesthesia practices, such as patient positioning and cricoid pressure utilization. Analysis in SPSS 26.0 involved descriptive and inferential analytics to explore practice patterns and relationships, with statistical significance established at p